The Influence of Workload and Agile Leadership on Performance Through Job Satisfaction as a Mediator of Personnel in the Assessment and Development Bureau of the Indonesian National Police Education and Training Institute : Pengaruh Beban Kerja dan Kepemimpinan Agile terhadap Kinerja Melalui Kepuasan Kerja sebagai Mediator Personel di Biro Penilaian dan Pengembangan Lembaga Pendidikan dan Pelatihan Kepolisian Nasional Indonesia - Monaputri, Ayu; Puji Wahono; Wolor, Christian Wiradendi (OGZ Research & Publishing, 2026)
This study aims to analyze the influence of workload and agile leadership on employee performance, with job satisfaction as a mediating variable. The research was motivated by the demand for improved employee performance in facing increasingly complex organizational dynamics that require high adaptability. The research methodology employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to 106 respondents. The data analysis technique used was Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between the research variables. The results showed that workload had a positive and significant effect on performance. Agile leadership also had a positive and significant effect on performance, and had the strongest influence on job satisfaction. Job satisfaction was shown to have a positive and significant effect on performance. Mediation tests revealed that job satisfaction partially mediated the relationship between workload and performance, as well as between agile leadership and performance. These findings confirm that improved performance is not only directly influenced by workload and agile leadership, but also through increased job satisfaction. Overall, this study concludes that appropriate workload management and the effective implementation of agile leadership play a crucial role in sustainably improving employee job satisfaction and performance.